(untitled) (Training and Practice : Journal of Educational Sciences, 2019)
For a long time, more and more research has been focused on exploring the specific abilities and motivations of generations Y and Z, and on working out effective strategies in order to develop them. The inspirational role of games was discovered centuries ago in pedagogy, in spite of the fact that only marketing and human management found a way finally how to make their customers and employees more motivated with game-experiences. The strategy is known as gamification and it has become increasingly popular mainly at public education level, but nowadays we can read about experiments in higher education as well. This study reports on the experience of a gamified course whose main goal was to increase students’ motivation towards learning.